Knowledge, attitude, and practice regarding shisha smoking in Jeddah, Saudi Arabia - Muhammad Anwar Khan; Syed Sameer Aga; Amro Abdulhaleem Noorwali; Mohammad Faisal Allaf; Waddah Adel Althagafi; Adnan Adel Bahashwan (Wolters Kluwer Medknow Publications, 2022)
Objectives: Shisha smoking in the middle east especially in Saudi Arabia is one of the traditional ways to consume tobacco which nowadays has transformed beyond just smoking tobacco and has become a style statement among youth across all generations and genders. The aim of this study was to assess the knowledge, awareness, and practice of public about the shisha smoking. Methodology: This cross-sectional study was carried out among the public of all levels in Jeddah from September 2018 through March 2019. A predesigned and validated questionnaire about shisha smoking was adopted to achieve the purpose of the study. Results: A total of 500 public responded to this survey, of them, 284 (56.8%) were males, while 216 (43.2%) were female; in addition, 294 (58.8%) were single and 328 (66.4%) had bachelor's degree. Around 200 (41.2%) were regular cigarette smokers while 185 (47.1%) were shisha smokers and only 94 (19.2%) smoked both. Among shisha smoker's majority of 75 (59.5%) smoked with friends and 53 (50.0%) shared their hose. In addition, most of the public agreed to the addictive nature of smoking in both forms, however, only 78 (18.4%) believed that shisha to be more addictive than cigarettes. Significant differences were found in smoking status, income, and years of smoking in between genders (P < 0.05). In addition, higher income and higher educational status were significantly associated with the habit of shisha smoking. Conclusions: This study found out the prevalence of smoking to be higher among surveyed public, especially shisha in both males and females. However, around 57% of the participants identified the need to quit it.